Food Risk Analysis: Towards a Better Understanding of “Hazard” and “Risk” in EU Food Legislation - Cioca, Ana-Andreea; Tušar, Livija; Langerholc, Tomaž (Foods, 2023)
For risk communication, it is important to understand the difference between “hazard” and “risk”. Definitions can be found in Codex Alimentarius and the European Union (EU) General Food Regulation (EC) No. 178/2002. The use of these terms as synonyms or their interchange is a recurrent issue in the area of food safety, despite awareness-raising messages sent by EFSA (European Food Safety Authority) and other interested entities. A quick screening of the EU’s food regulations revealed several inconsistencies. Hence, it was considered necessary to further investigate if regulations could act as a source for this problem. A software tool was developed to support the detection and listing of inconsistent translations of “hazard” and “risk” in certain EU food regulations. Subsequently, native-speaking experts working in food safety from each EU country were asked to provide their individual scientific opinion on the prepared list. All data were statistically analysed after applying numerical scores (1–5) describing different levels of consistency. Results showed that the most common problem was the interchange of “hazard” with “risk” and vice versa. This lack of consistency can create confusion that can further translate into misjudgments at food risk assessment and communication levels.